2011
DOI: 10.1155/2011/978312
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in p53 Research and Cancer Treatment

Abstract: TP53, encoding p53, is one of the most famous tumor suppressor genes. The majority of human cancers demonstrate the inactivation of the p53 pathway. Mutant p53 not only, no longer, functions as a tumor suppressor but can also exert tumor-promoting effects. The basic function of p53 is to respond to cellular stress. We herein review the recent advances in p53 research and focus on apoptosis, cell cycle arrest, and senescence in response to stress. We also review the clinical applications of p53-based therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 66 publications
2
120
0
3
Order By: Relevance
“…The analysis of histological situation of neoplasias shows the predominance of low differentiated forms of cancer (the most common malignant tumors of the uterus, thyroid, breast cancer in Ukraine) in woman [16,17]. There are tumors of moderate and high degree of malignancy with increased aggressiveness and the growth of metastatic ability of cancerous tissue in each subsequent accident.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of histological situation of neoplasias shows the predominance of low differentiated forms of cancer (the most common malignant tumors of the uterus, thyroid, breast cancer in Ukraine) in woman [16,17]. There are tumors of moderate and high degree of malignancy with increased aggressiveness and the growth of metastatic ability of cancerous tissue in each subsequent accident.…”
Section: Discussionmentioning
confidence: 99%
“…Ovaj protein se nagomilava u tumorskim ćelijama i može se dokazati imunohistohemijskim metodama. Kod bolesnika sa pozitivnim p53 preživ-ljavanje je bilo statistički značajno lošije nego kod bolesnika sa negativnim p53 (52,5 % vs. 94,1%) [6][7][8][9].…”
Section: Uvodunclassified
“…Nekoliko studija ispituje korelaciju između ekspresije proteina p53 i apoptoze kod kolorektalnih neoplazmi [5,6]. U našoj studiji analiza preživljavanja pacijenata u periodu od 7 godina pokazala je statistički značajnu razliku u preživljavanju pacijenata sa jako pozitivnim vrijednostima p53 i slabo pozitivnim vrijednostima p53 (p < 0,001).…”
Section: Diskusijaunclassified
“…Furthermore, most evidence suggests that the key contribution of p53 to apoptosis is primarily dependent on transcriptional activity. p53 has the ability to activate transcription of various proapoptotic genes, including those encoding members of the Bcl-2 family, such as the BH-3 only proteins Bax, Noxa, and Puma [31]. In addition, it has been found that when the p53 mutant was silenced, it resulted in reduced cellular colony growth in human cancer cells, which was found to be due to the induction of apoptosis.…”
Section: P53mentioning
confidence: 99%